Non-invasive early diagnosis of deep vein thrombosis - Zainal Abidin, Ahmad Noor Ariff (2015)
Deep Vein Thrombosis (DVT) is a blood clot that forms in deep veins which commonly occur in lower limb or thigh. The blood clot blocks deep vein and can travel to lung and block pulmonary arteries. This condition will cause fatal Pulmonary Embolism (PE). DVT can be diagnosed using non-invasive technique such as ultrasonography. One of the factors that cause the deep vein thrombosis occurs is the behaviour of vein valve. Therefore, the movement of vein valve needs to track to make further analysis of its behaviour for early detection of Deep Vein Thrombosis system. The aim of this project is to track the vein valve movement for early diagnosis of DVT. Distance between two nearest pixels with value 1 and reference line is proposed to be the method to track vein valve movement. The idea of this technique is the smallest distance of nearest pixels to reference line means the vein valve is closed. The distance for each differencing frame is plotted to see the sequence of distance pattern of vein valve closure. Baseline is created via observation (eye) method for experimental programme. The percentage difference between vein valve closure times of result from automatic tracking and baseline is 3.57%. Therefore, it showed that the proposed method is applicable and able to tracking the vein valve movement.